Specific expression network analysis of diabetic nephropathy kidney tissue revealed key methylated sites. Issue 10 (8th May 2018) - Wang, Yan‐Zhe; Xu, Wen‐Wei; Zhu, Ding‐Yu; Zhang, Nan; Wang, Yong‐Lan; Ding, Miao; Xie, Xin‐Miao; Sun, Lin‐Lin; Wang, Xiao‐Xia
Abstract : Diabetic nephropathy (DN) is one of the most common and serious complication in diabetes patients. However, the evidences of gene regulation mechanism and epigenetic modification with DN remain unclear. Therefore, it is necessary to search regulating genes for early diagnosis on DN. We identified tissue specific genes through mining the gene expression omnibus (GEO) public database, enriched function by gene ontology (GO), and kyoto encyclopedia of genes and genomes (KEGG) analysis, and further compared tissue‐specific network. Meanwhile, combining with differentially methylated sites, we explored the association epigenetic modification with the pathogenesis of DN. Glomeruli (Glom) may be the main tissue of signal recognition and tubulointerstitium (Tub) is mainly associated with energy metabolism in the occurrence of DN. By comparing tissue‐specific networks between Glom and Tub, we screened 319 genes, which played an important role in multiple tissue on kidney. Among them, ANXA2, UBE2L6, MME, IQGAP, SLC7A7, and PLG played a key role in regulating the incidence of DN. Besides, we also identified 1 up‐regulated gene (PIK3C2B) and 39 down‐regulated genes (POLR2G, DDB1, and ZNF230, etc.) in the methylated data of Glom specific genes. In the Tub specific expressed genes, we identified two hypo‐methylated genes (PPARA and GLS). Tub mainly caused abnormal energy metabolism, and Glom caused the changes in cell connections and histone modification. By analyzing differentially methylated sites and tissue‐specific expressed genes, we found the change of methylated status about the core regulating genes may be a potential factor in the pathogenesis of DN. Abstract : We found that Tub mainly causes abnormal energy metabolism, and glom causes the changes in cell connections and histone modification. Besides, we also found the change of methylated status about core regulating genes may be a potential factor in the pathogenesis of DN and some tissue specific genes and differentially methylated sites associated with DN based on the GEO database may provide new targets to better treat DN. Further, our study will be of great theoretical significance in guiding research on the diagnosis and treatment of DN in the future.